2013
DOI: 10.1586/17434440.2013.811867
|View full text |Cite
|
Sign up to set email alerts
|

Public preferences for colorectal cancer screening tests: a review of conjoint analysis studies

Abstract: A wide range of screening technologies is available for colorectal cancer (CRC) screening. There is demand to discover public preferences for these tests on the rationale that tailoring screening to preferences may improve uptake. This review describes a type of study (conjoint analysis) used to assess people's preferences for CRC screening tests and critically evaluates research quality using a recently published set of guidelines. Most primary studies assessed preferences for colonoscopy and faecal occult bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 35 publications
(60 reference statements)
1
36
0
Order By: Relevance
“…DCEs have been applied to numerous healthcare contexts,23 including bowel cancer screening,24 although these have assessed preferences for different bowel screening tests and not modifiable attributes of a single, specific investigation. DCEs are based on the premise that an aspect of healthcare may be defined by several key attributes (eg, bowel preparation), and each attribute may take one of several levels (eg, non-laxative, reduced-laxative or full-laxative preparation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DCEs have been applied to numerous healthcare contexts,23 including bowel cancer screening,24 although these have assessed preferences for different bowel screening tests and not modifiable attributes of a single, specific investigation. DCEs are based on the premise that an aspect of healthcare may be defined by several key attributes (eg, bowel preparation), and each attribute may take one of several levels (eg, non-laxative, reduced-laxative or full-laxative preparation).…”
Section: Methodsmentioning
confidence: 99%
“…The study was designed in accordance with the best practice guidelines for DCEs26 and following a review of the strengths and weaknesses of the literature 24. The three attributes selected were (1) the method of bowel preparation (specifically the intensity of the laxative effect), (2) test sensitivity for ≥10 mm precancerous polyps and (3) test specificity.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years in Europe and the United States, conjoint analysis, one of the stated preference techniques, is used for quantitative assessment of preferences for conditions allowing or promoting participation in cancer screening (Gyrd-Hansen and Sogaard, 2001;Marshall et al, 2007;Hawley et al, 2008;Hol et al, 2010;Ghanouni et al, 2013). In the past, it has been pointed out that the factors receiving emphasis are difficult to identify by reciprocal comparisons of multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, it should be taken into account that stated preferences as elicited with this study may differ from the revealed preference for screening policy of respondents. Concrete examples of this can be found for colon cancer screening, for which a review found that 66% to 88% stated they would be willing to attend, whereas actual attendance in the population was much lower (40%-50%) [21,22]. Also, there is uncertainty in our results because of the inherent difficulty respondents may experience when translating their preferences into rankings or numbers.…”
Section: Discussionmentioning
confidence: 97%
“…These types of methods are increasingly used in health care [15,17], but no results from stated preference studies for lung cancer screening are known [18]. There have, however, been stated preference studies in the context of screening for other types of cancer, namely, breast [16], colorectal [9,[19][20][21][22], and prostate [23][24][25] cancer. Common findings in these studies were that the most important attribute according to respondents was test accuracy, and that respondents indicated a higher willingness to attend if they had a higher self-perceived risk of cancer.…”
Section: Introductionmentioning
confidence: 99%